EuReCa_Srbija 2014-2021 - Analysis of data on non-initiation of CPR in relation to the age of patients with VBSZ - VasiliC, Milica; Bandulaja, Marina; Susković Bosancic, Rajka; Medic, Sara; Ristic, Jovana (Journal Resuscitatio Balcanica, 2024)
Objectives: Sudden out-of-hospital cardiac arrest represents a significant public health issue as the third leading cause of death worldwide. The annual incidence of OHCA in Europe ranges between 67 and 170 cases per 100,000 inhabitants, although it is believed that the actual number might be higher. Despite the measures taken and the attention drawn to the importance of this issue, both among healthcare professionals and the general population, the survival rate remains below 10%. Early recognition of cardiac arrest, initiation of CPR, and early defibrillation significantly improve survival and long-term outcomes in survivors of OHCA. Materials and Methods: The study included epidemiological data on OHCA collected through the European Resuscitation Council’s EuReCa study questionnaires, covering the period from October 1, 2014, to December 31, 2021. Variables are presented as frequencies and percentages. Analytical statistical steps included the Chi-square test to examine the association between categorical variables and the Fisher exact probability test. Results: A total of 8,349 OHCA cases were recorded during the observed period. Out of that number, CPR was initiated in 2,758/8,349 cases (33.1%). A statistically significant difference was observed depending on the age group of the patients (χ2 (3) = 225.376; p<0.001). A statistically significant difference in the frequency of initiating/not initiating CPR measures between genders was also observed in the age groups of 40 to 60 years (χ2 (1) = 5.072; p=0.024) and over 60 years (χ2 (1) = 271.585; p<0.001), while no statistically significant difference was observed in other age categories. In the group of patients in whom CPR measures were initiated, a statistically significant difference in the frequency of return of spontaneous circulation (ROSC) at the scene was observed among different age groups (χ2(3)=16.764; p<0.001). However, this difference was not observed when comparing the frequency of admission to the nearest hospital with spontaneous circulation (χ2(3)=4.342; p=0.227). Conclusion: This study is the first in Serbia to address the issue of initiating or not initiating cardiopulmonary resuscitation depending on the age of patients with out-of-hospital cardiac arrest. Our data indicate a significantly higher percentage of non-initiated resuscitations compared to the European average. Notably, the highest percentage of non-initiated resuscitations is recorded among older patients. The observed differences in the frequency of initiating CPR between genders, particularly among older women, also require further research to understand and potentially reduce existing inequalities.